Pertanggungjawaban Hukum Terhadap Tindakan Malpraktik Tenaga Medis di Rumah Sakit - Ismail Koto; Erwin Asmadi (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2021)
This article aims to find out the legal arrangements and liability related to malpractice acts in hospitals. The liability for criminal acts of malpractice is currently an important spotlight because the legal rules governing it are still vague. This is because the qualifications of malpractice acts are not clearly stated in the legal rules. These malpractice acts cannot be seen solely from a scientific point of view, but from a legal perspective too. Malpractice acts contain criminal and civil elements, this should be considered so that each party does not give their interpretations according to their respective knowledges. The research method used in this study is normative juridical by applying library research and conceptual approaches which will then be analyzed using Wetsen Rechtshitorische Interpretatie, grammatical interpretation, and systematic interpretation. Since the independence time until now, Indonesia has experienced three times of the Health Law enactment. The regulations related to medical malpractice in the Health Law state that, in the event that health workers are suspected of negligence in carrying out their profession, the negligence must be resolved first through mediation.